Population dynamics and exploitation level of green-lipped mussel (Perna viridis) using FiSAT from the offshore island of the Cox's Bazar Coast of Bangladesh - Sarker, Mohammad Nurul Amin; Abdul Halim, Mohammad; Barua, Mitu; Mohammad Zafar; Arshad, Aziz (Universiti Putra Malaysia Press, 2005)
Planning and management of molluscan resources require knowledge of various population parameters and exploitation level (E) of the population in a particular location. Estimation of population parameters like asymptotic length (L8), growth co-efficient (K), mortalities, exploitation level (E) and recruitment pattern of green-lipped mussel (Perna viridis) in the offshore Island of Cox’s Bazar coast of Bangladesh were studied by using the length frequency based analysis of FiSAT software. Asymptotic length (L8) was 19.43 cm and growth co-efficient (K) was estimated at 0.56/yr. Total mortality (Z) was 1.44/yr. Natural mortality (M) and fishing mortality (F) were 1.38/yr and 0.06/yr, respectively. Exploitation level (E) of R viridis was 0.04 while the maximum allowable limit of exploitation value (Emax) was 0.68. The exploitation level (< 0.50) indicates that the stock of P. viridis might underexploited in the offshore Island of the Cox’s Bazar coast of Bangladesh.